Enhancing online learning with Wakelet: A technology acceptance framework analysis - Quah, Wei Boon (Journal of Social, Humanity, and Education, 2023)
Purpose: This study aims to examine students’ perceived usefulness, perceived ease of use, behavioral intentions, and attitudes toward the use of Wakelet as an interactive digital platform for teaching and learning (T&L) in Front Office modules. Research methodology: The sample of respondents was composed of twenty-four Front Office students enrolled in the Hotel Operation program, and the research instrument was a questionnaire based on the Technological Acceptance Model. Results: The findings indicate that the majority of respondents accept the use of Wakelet as an interactive digital platform for T&L in Front Office modules, and Wakelet is also easy to use. Additionally, respondents' attitudes were positive toward the use of Wakelet, and students' behavioral intentions towards the use of Wakelet were also at a high level. Limitations: However, this study has limitations, such as focusing only on students' perceptions and attitudes towards Wakelet as a digital platform for T&L in the Front Office module. Contribution: This research adds to the body of knowledge by providing insights into students' perceptions of Wakelet as a new interactive digital platform for T&L in the Front Office module. It highlights the positive attitudes and perceived usefulness of Wakelet among students, indicating that Wakelet has the potential to enhance the quality of online learning experiences. Novelty: The novelty of this study lies in its examination of the perceptions, attitudes, and behavioral intentions of students towards Wakelet as a new digital platform for teaching and learning. This study provides evidence that Wakelet can be an effective tool for enhancing the learning experience and improving student performance.